SOCIOCULTURAL METRICS OF THE PERSONAL PARADIGM OF ORPHANS’ UPBRINGING IN PEDAGOGICAL THEORY AND PRACTICE OF UKRAINE - Popovych; Lialiuk, Galina; Aleksieieva, Mariia; Popovych, Antonina; Bondarenko, Viktoriia; Kovtun, Oksana; Tsiuniak, Oksana (Revista Inclusiones, 2019)
The purpose of the article is to outline and analyze the sociocultural metrics of paradigm of orphans’ upbringing in Ukraine. The philosophical and educational methodology for the formation and development of a new paradigm in the context of social change is proposed. The methodological basis of the research was the analysis, systematization and generalization of ideas, concepts, definitions, approaches, provisions for understanding the upbringing of orphans, features of the development of care-educational activity in Ukrainian and foreign pedagogical theory. The authors propose the definition of “care-educational activity” and analyze the main approaches to the definition of care-educational activity. “Care-educational activity” is considered as a purposeful, appropriately planned set of actions and activities of a social educator, a psychologist, tutors, in order to provide for the basic needs of orphans and children deprived of parental care. Emphasis is placed on the vital needs, favorable conditions for the comprehensive development of the individual, the needs of normalizing the mental state of the orphan and the actualization of the immediate development’s area. The importance of the social situation, establishing relations with the environment, socialization, social readaptation and reintegration in the society are outlined.